Incidence and risk factors of homicide-suicide in Swiss households: National Cohort study. - Radoslaw Panczak (Public Library of Science (PLoS), 2013)
Background Homicide-suicides are rare but catastrophic events. This study examined the epidemiology of homicide-suicide in Switzerland. Methods The study identified homicide-suicide events 1991-2008 in persons from the same household in the Swiss National Cohort, which links census and mortality records. The analysis examined the association of the risk of dying in a homicide-suicide event with socio-demographic variables, measured at the individual-level, household composition variables and area-level variables. Proportional hazards regression models were calculated for male perpetrators and female victims. Results are presented as age-adjusted hazard ratios (HR) with 95% confidence intervals (95%CI). Results The study identified 158 deaths from homicide-suicide events, including 85 murder victims (62 women, 4 men, 19 children and adolescents) and 68 male and 5 female perpetrators. The incidence was 3 events per million households and year. Firearms were the most prominent method for both homicides and suicides. The risk of perpetrating homicide-suicide was higher in divorced than in married men (HR 3.64; 95%CI 1.56-8.49), in foreigners without permanent residency compared to Swiss citizens (HR 3.95; 1.52-10.2), higher in men without religious affiliations than in Catholics (HR 2.23; 1.14-4.36) and higher in crowded households (HR 4.85; 1.72-13.6 comparing ≥2 with <1 persons/room). There was no association with education, occupation or nationality, the number of children, the language region or degree of urbanicity. Associations were similar for female victims. Conclusions This national longitudinal study shows that living conditions associated with psychological stress and lower levels of social support are associated with homicide-suicide events in Switzerland.